Pelatihan Penggunaan Teknologi Sederhana Untuk Pengajaran dan Pembelajaran Bahasa Inggris - Mali, Yustinus Calvin Gai (Jurnal Pengabdian UntukMu NegeRI, 2025)
This Community Service activity (PkM) aims to train the use of simple technology to support English as a Foreign Language (EFL) teaching and learning activities. This PkM activity, in the form of training, was carried out online through the Google Meet platform on Friday, November 3, 2023, at 07.30-09.00 WIB. The main participants of this training were 10 English teachers who were students of the 2023 Teacher Profession Program in Service (PPG-Daljab) at the English Education Study Program, Satya Wacana Christian University. In the material presentation session, the author introduced various technologies and their potential to support EFL teaching and learning practices. Some of the potentials explored from the technology include searching for descriptive reading texts of famous people from around the world, displaying word clouds related to the most occurring (English) vocabulary in a reading text, presenting vocabulary exercises in English in a more interesting way, searching for English learning materials online, and practicing finding the meaning and pronouncing vocabulary in English. In the session, the participants and the author try the technology. Finally, the author asked the participants to evaluate the training session presented by the author.